The Protective Effect of Alpha-Mangostin against Cisplatin-Induced Cell Death in LLC-PK1 Cells is Associated to Mitochondrial Function Preservation - Laura María Reyes-Fermín; Sabino Hazael Avila-Rojas; Omar Emiliano Aparicio-Trejo; Edilia Tapia; Isabel Rivero; José Pedraza-Chaverri (MDPI AG, 2019)
Cis-dichlorodiammineplatinum II (CDDP) is a chemotherapeutic agent that induces nephrotoxicity by different mechanisms, including oxidative stress, mitochondrial dysfunction, autophagy, and endoplasmic reticulum stress. This study aimed to evaluate if the protective effects of the antioxidant alpha-mangostin (αM) in CDDP-induced damage in proximal tubule Lilly laboratory culture porcine kidney (LLC-PK1) cells, are related to mitochondrial function preservation. It was found that αM co-incubation prevented CDDP-induced cell death. Furthermore, αM prevented the CDDP-induced decrease in cell respiratory states, in the maximum capacity of the electron transfer system (E) and in the respiration associated to oxidative phosphorylation (OXPHOS). CDDP also decreased the protein levels of voltage dependence anion channel (VDAC) and mitochondrial complex subunits, which together with the reduction in E, the mitofusin 2 decrease and the mitochondrial network fragmentation observed by MitoTracker Green, suggest the mitochondrial morphology alteration and the decrease in mitochondrial mass induced by CDDP. CDDP also induced the reduction in mitochondrial biogenesis observed by transcription factor A, mitochondria (TFAM) decreased protein-level and the increase in mitophagy. All these changes were prevented by αM. Taken together, our results imply that αM’s protective effects in CDDP-induced toxicity in LLC-PK1 cells are associated to mitochondrial function preservation.